1993
DOI: 10.1163/156853993x00588
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Acoustic Correlates in Vocal Exchange of Coo Calls in Japanese Macaques

Abstract: Vocal exchanges of coo calls in female Japanese macaques were observed in two populations. Temporal patterns of occurrence of these vocalizations during vocal interaction were studied by analyzing inter-call intervals between two consecutive coos. When the second call was uttered by a different caller from the first (DC sequence), most of the second calls occurred at intervals shorter than approximately 0.8 sec, and the remaining ones at intervals longer than approximately 0.8 sec. These results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 21 publications
8
44
0
Order By: Relevance
“…Contact calls are produced by most members of a troop in a variety of contexts, but always affiliative [15]. Previous studies on contact calls of Japanese macaques have demonstrated individual recognition [16] as well as exchange rules [15], including turn-taking [17], acoustic matching between callers [18] and persistent waiting for a response [19].…”
Section: Introductionmentioning
confidence: 99%
“…Contact calls are produced by most members of a troop in a variety of contexts, but always affiliative [15]. Previous studies on contact calls of Japanese macaques have demonstrated individual recognition [16] as well as exchange rules [15], including turn-taking [17], acoustic matching between callers [18] and persistent waiting for a response [19].…”
Section: Introductionmentioning
confidence: 99%
“…Here, I found that animals were more likely than expected to produce a signature whistle in the five seconds following their partner's signature whistle. Vocal exchanges where a receiver responds to a produced signal by replying with its own signal have been reported in many animals ranging from primates (Sugiura, 1993(Sugiura, , 1998Miller et al, 2009) to song birds (Krebs et al, 1981) to odontocetes . Thus, the observed increase in probability of a signature whistle is consistent with the hypothesis that animals are responding to each other's signature whistles by producing their own signature whistles.…”
Section: Discussion Iii: Response Latency and Inter-animal Calling Bementioning
confidence: 99%
“…Sharng may improve the receiver's ability to identify environmental effects on a propagating signal, which may improve the receiver's ability to estimate the range to the signaler (Morton, 1982;Falls et al, 1982;McGregor et aI., 1983;Shy & Morton, 1986; but see Naguib, 1997Naguib, , 1998Wiley, 1998). Matched counter-callng occurs when a receiver responds to a signal by producing the same signal (Sugiura, 1993), and may provide a mea!1s for a respondent to direct a signal at the original caller (McGregor et aI., 1992).…”
Section: Discussionmentioning
confidence: 99%